Photosynthesis From Its Evolution to Future Improvements in Photosynthetic Efficiency Using Nanomaterials - Cristóbal García Cañedo, Juan; Lorena López Lizárraga, Gema (IntechOpen, 2018)
This book is a compilation. It starts from the origins of the photosynthetic capacity of organisms with a summary of the evolution of photosynthesis. This is followed by a concise description of the photosynthetic process and a discussion of the role that light, nutrients, and cultivation play in the photosynthetic process using examples in each case. Finally, the book explains future improvements in the field by applying nanotechnology to improve photosynthetic productivity, explaining how crop productivity can be increased by engineering crop plants for tolerance against various environmental stresses and improving yield attributes, especially photosynthetic efficiency using nanomaterials.